2017
DOI: 10.1088/1674-1056/26/1/015204
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser induced nanostructuring of zirconium in liquid confined environment

Abstract: The surface, structural, and mechanical properties of zirconium after irradiation with Ti: sapphire laser (800 nm, 30 fs, 1 kHz) have been investigated. The zirconium targets were exposed for a varying number of laser pulses ranging from 500 to 2000 at a fixed fluence of 3.6 J/cm 2 corresponding to an intensity of 1.2×10 14 W/cm 2 in ambient environments of deionized water and propanol. A scanning electron microscope (SEM) was employed to investigate the surface morphology of the irradiated zirconium. The SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The possibility of using laser light as a convenient and versatile tool for sculpting micro-and nano-structures has prompted the recent renewed interest in the multi-functional material systems. [1][2][3][4][5] Many interesting works, such as micronano scale ripples, [3] nano-sponges, [6] and subwavelength ripples, [5] have been reported by laser direct writing technique. In 2016, Terakawa et al demonstrated the construction of three-dimensional (3D) metal microstructures in biocompatible poly-based hydrogel by laser-induced photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using laser light as a convenient and versatile tool for sculpting micro-and nano-structures has prompted the recent renewed interest in the multi-functional material systems. [1][2][3][4][5] Many interesting works, such as micronano scale ripples, [3] nano-sponges, [6] and subwavelength ripples, [5] have been reported by laser direct writing technique. In 2016, Terakawa et al demonstrated the construction of three-dimensional (3D) metal microstructures in biocompatible poly-based hydrogel by laser-induced photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…This ripple formation can also be attributable to the interaction of ns laser radiation with the surface electromagnetic waves (SEW) formed during the laser interaction of the material [39]. The excitation of surface plasmon polaritons (SPPs) induces the periodic enhancement of local fields in the surface layer.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrous structures like nanoscale ripples appear on the irradiated area of Figure 2a, along with droplets and cavities. Heating induced by laser causes thermal desorption, thermal ablation and explosive boiling after melting of the irradiated area which results in cavity formation [35] and the hydro-dynamical effects are responsible for the formation of droplets. With the increase of fluence, the fibrous structures are transformed to micro-cones exhibited in Figure 2c,d.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the reduced hardness can be related to crystal growth due to diffusion of O across the grain boundaries and tensile residual stresses causing enhancement in the cavity density and cavity size (Figure 4). From Figure 10, it is observed that the hardness variation directly depends on the crystallite size, O diffusion and presence of residual stresses [35].…”
Section: Resultsmentioning
confidence: 99%